2019
DOI: 10.5614/j.math.fund.sci.2019.51.2.3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Root Extract of Ruellia tuberosa L. on Kidneys of Diabetic Rats

Abstract: The aim of this research was to study the antidiabetic activity of root extract of Ruellia tuberosa L. on rats (Rattus novergicus) induced by multiple low doses of streptozotocin. The parameters investigated were blood glucose levels, protease activities, and the histopathologic profiles of the kidneys. Three groups of rats, i.e. control, diabetic, and treatment, were used. R. tuberosa L. extracts were given orally for treatment at a dose of 250 mg/kg body weight per day for 21 consecutive days. The induced di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 14 publications
0
12
0
1
Order By: Relevance
“…After adaptation, rats were divided into five groups ( n = 5 in each group): control (group 1); diabetic (group 2); diabetic that treated with 250 mg/kg body weight extracts per day (group 3); diabetic that treated with 375 mg/kg body weight extracts per day (group 4); and diabetic that treated with 500 mg/kg body weight extracts per day (group 5). The extract doses were chosen based on the doses applied to our previous study [ 17 ]. Diabetes mellitus was induced by STZ injection intraperitoneally with 20 mg/kg body weight in 100 mL of citrate buffer for five days consecutively.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…After adaptation, rats were divided into five groups ( n = 5 in each group): control (group 1); diabetic (group 2); diabetic that treated with 250 mg/kg body weight extracts per day (group 3); diabetic that treated with 375 mg/kg body weight extracts per day (group 4); and diabetic that treated with 500 mg/kg body weight extracts per day (group 5). The extract doses were chosen based on the doses applied to our previous study [ 17 ]. Diabetes mellitus was induced by STZ injection intraperitoneally with 20 mg/kg body weight in 100 mL of citrate buffer for five days consecutively.…”
Section: Methodsmentioning
confidence: 99%
“…had shown antidiabetic activity through in vivo studies [ 16 , 17 ]. These effects included decreasing blood glucose concentrations, lowering levels of MDA, and showing improvements on the kidney histopathological profiles [ 16 , 17 ]. Phytochemical examination of this study showed that n -hexane R. tuberosa L .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study is investigating the activity from secondary metabolites compounds contained in R. tuberosa L. root extracts using in silico molecular docking approach. Based on our previous studies, R. tuberosa L. mostly contained flavonoids and phytosterol compounds [15,16]. In addition, the R. tuberosa L. hydroethanolic extracts have showed anti-diabetic activity in an in-vivo study [17][18][19].…”
Section: Introductionmentioning
confidence: 98%
“…Based on our previous studies, n-hexane root extracts from R. tuberosa L. have activity as an antidiabetic drug in rat diabetic models [10]. ese results were shown by blood glucose reduction, MDA level decrease, and kidney histopathological profile recovery [10]. A qualitative test has demonstrated that triterpenoid compounds were present in the n-hexane R. tuberosa L. root extracts.…”
Section: Introductionmentioning
confidence: 99%